THE CORRELATION BETWEEN OF NUTRITIONAL STATUS AND COGNITIVE DEVELOPMENT - FITRIANI, INNA SHOLICHA (Jurnal Keperawatan, 2017)
Nutrition becomes an important part in the role of mental and physical health for toddlers. In Ponorogo there are three villages with a population of the majority are living with down syndrome, one of them is sidoharjo village, Jambon, with 323 people where toddlers till adult 40 years has the most Down Syndrom attact. One of  factor that coused down syndrome is the low coverage of nutrition that impact on the level of intelligence. This research used analytic survey technique with cross sectional method. This research use 129 respondents then data collect with spearman rho analysis. The results obtained is the value of sig ( 2 ? tailed) or value probalility (p) compared to standard significance 5 % ( 0,05 ) the result is value 0,037 < 0,05 thus , nutritional status had correlation between cognitive development in toddlers under 5 years.